Absence of a diurnal rhythm of oxytocin and arginine-vasopressin in human cerebrospinal fluid, blood and saliva. (December 2019) - Kagerbauer, Simone Maria; Debus, Jennifer Muriel; Martin, Jan; Gempt, Jens; Jungwirth, Bettina; Hapfelmeier, Alexander; Podtschaske, Armin Horst
Abstract: Purpose: The aims of our study were to determine first circadian influences on central concentrations of the neuropeptides oxytocin and arginine-vasopressin and second to investigate if these central concentrations are associated with those in the peripheral compartments blood and saliva in neurocritical care patients. We therefore included patients with external ventricular drain who attended a neurosurgical intensive care unit and were not exposed to painful or stressful stimuli during the sampling period. For this purpose, blood, cerebrospinal fluid and saliva were collected in a 24-hour-interval at the timepoints 06:00, 12:00, 18:00 and 24:00. Results: In none of the three body fluids examined, significant time-dependent fluctuations of oxytocin and arginine-vasopressin concentrations could be detected during the 24-hour sampling period. The only exception was the subgroup of postmenopausal women whose oxytocin concentrations in cerebrospinal fluid at 12:00 were significantly higher than at 18:00. Correlations of blood and cerebrospinal fluid and blood and saliva neuropeptide levels were very weak to weak at each timepoint. Cerebrospinal fluid and saliva oxytocin levels showed a moderate correlation at 06:00 but did correlate very weak at the other timepoints. Conclusions: Central as well as peripheral oxytocin and arginine-vasopressin concentrations in neurocritical care patients did not show significant diurnal fluctuations. No strong correlations between central and peripheral neuropeptide concentrations could be detected under basal conditions. If investigators even though decide to use saliva concentrations as surrogate parameter for central neuropeptide activity, they have to consider that correlations of cerebrospinal fluid and saliva oxytocin seem to be highest in the early morning. Highlights: Diurnal variations of central neuropeptide concentrations have been described in several species including humans We could not show circadian rhythmicity of central OXT and AVP levels in neurocritical care patients under basal conditions No strong correlations between central and peripheral neuropeptide concentrations could be detected Correlations of oxytocin CSF and saliva levels may depend on the timepoint of sampling